Biofertilizing Effect of Soil Cyanobacterium Anabaena cylindrica–Based Formulations on Wheat Growth, Physiology, and Soil Fertility - Zineb Hakkoum; Farah Minaoui; Amer Chabili; Mountasser Douma; Khadija Mouhri; Mohammed Loudiki (Agriculture)
Cyanobacteria are well known for their biofertilizing capacities, which can enhance soil fertility and plant growth. This study aims to evaluate the biofertilizing effects of the indigenous nitrogen-fixing soil cyanobacterium Anabaena cylindrica on the growth, biochemical, and physiological responses of wheat, as well as soil fertility. Medium filtrate, aqueous extract, sonicated culture, and crude culture of A. cylindrica at different doses (50%, 25%, 1%, and 0.2% v/v) were applied using a soil drench under greenhouse conditions. After 40 days of growth, all cyanobacterial suspensions significantly increased wheat growth, biochemical properties, and plant mineral composition compared to the controls. The greatest improvements were observed with the application of cyanobacterial suspensions at the highest concentrations, 25% and 50%. These doses also significantly enhanced the nutritional and physicochemical properties of the soil. Among the different treatments, soil inoculation with crude culture (living cells) and growth medium filtrate at 50% were the most efficient. The wheat growth–promoting effect was attributed to the intracellular or released bioactive compounds of A. cylindrica, such as polysaccharides, proteins, indole acetic acid phytohormone, nitrogen, phosphorus, and potassium. This study demonstrates that terrestrial A. cylindrica-derived suspensions promote wheat growth and can be used as an effective and eco-friendly biofertilizer to enhance plant growth and crop productivity.